Local Wisdom of The Mentawai Tribe Community on Siberut Island in The Vicinity of Maritime Tourism Area - Munandar, Anis; Noer, Melinda; Erwin; Syahni, Rahmat (Mudra Jurnal Seni Budaya, 2024)
The tourism sector plays a role in the economic development of Indonesia and serves as one of the sources of Regional Original Income. Generally, countries with potential coastal natural resources utilize maritime tourism as a tool to support their development, including in the Mentawai Islands Regency, West Sumatra Province. The tourism sector represents one of the economic development potentials in the Mentawai Islands Regency. Maritime tourism involves recreational activities conducted in marine or coastal areas, including beaches, islands, and oceanic regions, encompassing the surface, depths, and seabed. One of the potentials of maritime tourism destinations is the local wisdom specific to each region. Areas that adopt a community-based approach to the development of maritime tourism utilize social and cultural potentials as tools for its advancement. Therefore, this study focuses on the local wisdom of the Mentawai ethnic community on Siberut Island within the maritime tourism region. The research aims to identify, describe, and explain the local wisdom still applied in the daily lives of the indigenous Mentawai community on Siberut Island as a basis for the development of maritime tourism. The theory of local wisdom is used to analyze the forms of local wisdom. The research design falls under the non-experimental research design. Based on its nature, qualitative data is utilized in the study. From the discussion, it can be concluded that the South Siberut and Southwest Siberut sub-districts exhibit various forms of local wisdom. The forms of local wisdom include knowledge, technology, religious beliefs, culture, customs, and creative products of the community.